ATMOSPHERIC PCO2 SINCE 60 MA FROM RECORDS OF SEAWATER PH, CALCIUM, AND PRIMARY CARBONATE MINERALOGY - Demicco R.V.; Lowenstein T.K.; Hardie L.A. (My University, 2003)
A 60 m.y. record of atmospheric pCO2 has been refined from knowledge of (1) secular changes in the major ion composition of seawater (particularly Ca and Mg) and (2) oscillations in the mineralogy of primary oceanic carbonate sediments. Both factors have had a significant impact on the chemistry of the ocean carbonate buffer system. Calculated atmospheric pCO2 oscillated between values of 100 300 ppm and to maxima of 1200 2500 ppm from 60 to 40 Ma and varied between 100 and 300 ppm from 25 Ma to the present. The refined pCO2 values are significantly lower than previous estimates made from seawater pH data where total dissolved inorganic carbon was assumed constant and more in line with modeling and stomatal index estimations of atmospheric pCO2 for the Tertiary.
Keywords: carbon dioxide; seawater chemistry variation; atmospheric history; equilibrium; geochemistry